Representasi Unsur Perbedaan Budaya dan Lingkungan Sosial Keluarga Imigran Korea-Amerika Pada Film ‘Minari’ - Sugiawati, Yeni (PT. Alahyan Publisher Sukabumi, 2023)
This research aims to describe the depiction of elements of cultural differences and the social environment of Korean-American immigrant families in the film Minari. Regarding different aspects of life in the two countries. The method used in this research is a descriptive method. The collection technique comes from the film Minari by Lee Isaac Chung and references to theoretical studies in research journals. Data analysis techniques begin with data reduction, data presentation, conclusions and verification. The results of the analysis of elements of cultural differences and the social environment of Korean-American immigrant families in the film Minari show aspects that can be compared, namely the language aspect used by Americans and David, who grew up in America, uses English, while his immigrant grandmother still uses South Korean. Different knowledge systems, livelihood systems for Korean immigrants who farm, technology systems used by American citizens and South Korean immigrants, the Yi family, as well as very different religious and artistic aspects. From this research it can be concluded that there are many adaptations that an immigrant must undergo when moving from one country to another, as did Jacob's family.